2018
DOI: 10.1021/acsami.8b07213
|View full text |Cite
|
Sign up to set email alerts
|

Triple Stimuli-Responsive Magnetic Hollow Porous Carbon-Based Nanodrug Delivery System for Magnetic Resonance Imaging-Guided Synergistic Photothermal/Chemotherapy of Cancer

Abstract: The premature leakage of anticancer drugs during blood circulation may the damage immune system, normal cells, and tissues. Constructing targeted nanocarriers with pH, glutathione, and NIR triple-responsive property can effectively avoid the leakage of anticancer drugs before they arrive at the targeted site. In this paper, magnetic hollow porous carbon nanoparticles (MHPCNs) were successfully fabricated as nanocarrier. Poly(γ-glutamic acid) was used to cap the pores of MHPCNs. The photothermal conversion prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 55 publications
0
51
1
Order By: Relevance
“…Earlier studies indicate that intraperitoneal administration of silver NPs induces cytoplasmic changes in liver and kidney tissues43 while intravenously administered silver NPs accumulate in different organs, including liver, kidney, spleen, brain and lungs 25. Another recent investigation demonstrated that magnetic hollow porous carbon NPs (MHPCNs) are primarily deposited in spleen, lung and liver 44…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies indicate that intraperitoneal administration of silver NPs induces cytoplasmic changes in liver and kidney tissues43 while intravenously administered silver NPs accumulate in different organs, including liver, kidney, spleen, brain and lungs 25. Another recent investigation demonstrated that magnetic hollow porous carbon NPs (MHPCNs) are primarily deposited in spleen, lung and liver 44…”
Section: Discussionmentioning
confidence: 99%
“…Carbon [139,140], gold [141], and upconversion nanoparticles (UCNPs) [142] were often utilized in NIR responsive drug carriers owing to their NIR absorption capacity. Lee and co-workers [139] fabricated the hollow mesoporous silica/carbon nanoparticles as a DOX carrier.…”
Section: Response To Near-infrared (Nir)mentioning
confidence: 99%
“…In the following year, Fang et al utilized graphene carbon dots to seal the pores, which also functioned as a robust PTT agent in the subsequent synergistic chemo/photothermal cervical cancer treatment. 80 A triple stimuli-response magnetic hollow porous carbon-based drug delivery system (MHPCNs–SS–PGA–FA/DOX) was developed by Wu et al 81 . The poly-γ-glutamic acid-capped shell of hollow NPs included an inner Fe 3 O 4 layer and a porous carbon outer layer.…”
Section: Photothermal-based Therapy For Cancer Treatmentmentioning
confidence: 99%